High-intensity interval training improves the reactive strength index and motor ability of youth football players - Kizilca, Serkan; Kahraman, Muhammed Zahit; Okut, Sedat; Arslan, Ersin; Bilici, Omer Faruk; Celik, Ismail; Bilici, Muhammed Fatih (Bmc, 2026)
Background: The aim of this randomized controlled trial was to determine the effects of a four-week running-based high-intensity interval training (HIIT) intervention on the reactive strength index (RSI) and motor abilities in youth football players. In this context, the contributions of the running-based HIIT protocol HIIT protocol, implemented in addition to regular football training, were evaluated on performance indicators such as speed, back strength, change of direction (COD), and countermovement jump (CMJ). This study aims to contribute to the development of scientifically grounded training programs to support performance improvement in youth football players. Methods: A quantitative research design was employed in this study, specifically a randomized pretest-posttest controlled experimental design. Twenty male youth football players, aged 11-13 years, who voluntarily participated in the study were randomly allocated to either the experimental group (EG; n = 10) or the control group (CON; n = 10). The EG participated in a running-based HIIT program three times per week for four weeks by replacing a low-to-moderate-intensity technical-tactical segment of their regular football training, whereas the CON continued with only regular football training during this period without any additional training volume. The players underwent RSI, 10 m, 20 m, and 30 m sprint tests, back strength tests, the Illinois Agility Test, and CMJ tests both before the training sessions and at the end of the four-week intervention. Results: According to the repeated-measures ANOVA results, pretest values did not differ significantly between the groups (p > .05). Over the 4-week period, significant improvements with large effect sizes were observed in RSI, sprint performance (10, 20, 30 m), back strength, COD, and CMJ tests (p < .05; eta p & sup2; = 0.29-0.55). Significant group & times; time interactions were also detected for all variables, again with large effect sizes (p < .05; eta p & sup2; = 0.20-0.30), indicating greater improvements in the EG compared to the CON. However, despite these favourable within-group changes, between-group post-test comparisons did not reach statistical significance. Conclusions: This study revealed that a 4-week HIIT intervention applied to youth male football players had positive effects on the RSI and motor abilities, as evidenced by large within-group improvements and significant group & times; time interactions, despite the absence of statistically significant between-group post-test differences. These findings suggest that HIIT protocols should be integrated into training programs as an effective strategy to improve explosive strength, COD, and overall functional performance in young athletes. Trial registration: This randomized controlled trial was retrospectively registered with ISRCTN (ISRCTN45188963) on 16 July 2025 due to administrative delays during ethics approval and registry processing.
Keywords: Adolescents; Motor Performance; Training Adaptation